2017
DOI: 10.1049/enb.2017.0003
|View full text |Cite
|
Sign up to set email alerts
|

Production of recombinant collagen: state of the art and challenges

Abstract: Collagen, which is often used in healthcare materials and biomedical research, is largely extracted from animal sources. Recombinant human collagen has the potential to be a promising alternative to animal collagen which has many shortcomings, including immunogenicity and lack of biocompatibility. Currently, recombinant human collagen has been expressed in both eukaryotic and prokaryotic hosts with varying degrees of success. One issue with recombinant collagen across all hosts is the inability to achieve full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 95 publications
0
43
0
3
Order By: Relevance
“…Cells such as fibroblast and chondrocytes which specialize in type I and type II collagen production respectively can be cultured and the synthesised collagen harvested from media or cell layers. Recombinant collagen production is using genetically engineered microorganisms, plants or animals such as bacteria, yeast, transgenic corn and silkworms [29,30]. Synthetic peptides mimicking collagen trimeric structure have also been investigated to produce collagen-like peptides [31,32].…”
Section: Sources Of Collagenmentioning
confidence: 99%
“…Cells such as fibroblast and chondrocytes which specialize in type I and type II collagen production respectively can be cultured and the synthesised collagen harvested from media or cell layers. Recombinant collagen production is using genetically engineered microorganisms, plants or animals such as bacteria, yeast, transgenic corn and silkworms [29,30]. Synthetic peptides mimicking collagen trimeric structure have also been investigated to produce collagen-like peptides [31,32].…”
Section: Sources Of Collagenmentioning
confidence: 99%
“…148 Pro-collagen (commercial collagen) is prepared from domesticated animals, including pigs and cows and has an increasing global demand. 149,150 Inauspiciously, it is liable to harbor human pathogens, comprising prions or viruses. 149 As a viable alternative, tobacco plants have been used to efficiently express human recombinant type I pro-collagen using transgenic technology.…”
Section: Production Of Collagenmentioning
confidence: 99%
“…This is due to the outbreak of transmissible diseases like bovine spongiform encephalopathy (BSE), transmissible spongiform encephalopathies (TSE) and foot-and-mouth disease (FMD) that pose threat to human (Jongjareonrak et al, 2005;Peng et al, 2012a;Silvipriya et al, 2015;Singh et al, 2011;Swatschek et al, 2002;Zhang et al, 2009). Furthermore, religious sentiments for Muslims, Jewish, and Hindus created another issue in the consumption of porcine or bovine-derived collagen (Sadowska et al, 2003;Singh et al, 2011;Souza, 2016;Wang et al, 2017). Islamic and Jewish believers are prohibited in the consumption of pork, whereas bovine sources are prohibited for Sikhs and Hindus (Eriksson et al, 2013;Herbert et al, 1994;Singh et al, 2011;Souza, 2016).…”
Section: Sources Of Collagenmentioning
confidence: 99%
“…Purification of recombinant bacterial collagen using a combination of precipitation and proteolysis by pepsin was performed in two out of three studies (Cao & Xu, 2008;Werkmeister & Ramshaw, 2015). Werkmeister, Singh, and coworkers reported that the application of precipitation and proteolysis is applicable to a wide range of bacterial collagen with different collagen domain sizes (Singh et al, 2011;Wang et al, 2017). The acid precipitation method can be considered as an efficient technique in removing a high amount of bacterial host proteins and they will tend to precipitate upon the addition of acid as host proteins were least soluble at a pH lower than 5 (Kiew & Don, 2013;Werkmeister & Ramshaw, 2015).…”
Section: Precipitationmentioning
confidence: 99%
See 1 more Smart Citation